THE EFL STUDENTS' PERCEPTION ON ONLINE LEARNING TOWARDS SPEAKING ABILITY - Eka Rochimatul Jannah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The aim of this study was to investigate students’ perception on online learning, students’ perception in interacting on online learning, problems in interaction, and students’ strategies. The data was gained by qualitative method using questionnaire and semi-structered interview. The participant of this research were sixth semester of Engllish Department of University of Islam Malang. In this study, Qualitative case study was used this research. Questionnaire and interviewed used to collect the data. Questionnaire was using English that was adopted from (Fitriani et al., 2020). The language of semi-structered interview used English was conducted online. The data was analyzed using (Sugiyono, 2015). From the data identification, students’ perception on online learning, most of the student did not agree that online learning could bring a positive effect on their speaking ability. Students found problems in interacting were on internet network, limited time and less interaction, and lack of vocabulary and practice. Fortunately, there were sixth strategies used by the students to overcome their problems for instance listening extensively, reading extensively, watching extensively, looking for fascinating topics, a lot of practicing speaking, and taking small notes.Keywords: Perception in Online Learning, Problems in Speaking